198 Diagnosed occupational contact dermatitis compared to occupational dermatitis workers' compensation claims: Are females less likely to claim workers' compensation?. (11th October 2013) - Keegel, G; MacFarlane,; Black,; Cahill,; Palmer,; Driscoll,; Nixon,; Smith,
Abstract : Objective: To compare diagnosed disease data for occupational contact dermatitis (OCD) with workers' compensation claims data for OCD, thereby characterising potential differences between the two information sources. Methods: We conducted a retrospective analysis of OCD diagnosed disease and workers' compensation claims data, for the twelve highest risk occupational groups for the state of Victoria, Australia from 1993–2009. Diagnosed disease data for OCD is collected by the Victorian Skin and Cancer Foundation, which services the state of Victoria. Workers' compensation claims for OCD are from the Compensation Research Database, which is held by the Institute for Safety, Compensation and Recovery Research. Estimates of denominators for the occupational groups are derived from 2001 Australian Bureau of Statistics census data. Results: The proportions for diagnosed disease and the workers' compensation claims datasets varied considerably by gender, age and occupational group. There was a much higher rate of females diagnosed with OCD compared to the rate of workers' compensation claims (48% for diagnosed disease dataset vs 33% for workers' compensation claims dataset, p < 0.001). These differences by gender were significant in the following occupational groups using diagnosed disease data compared to workers' compensation claims data: Hair and beauty, Automobile workers, Science workers, Trades persons and labourers, Food handlers, and Process workers and packers (p < 0.05). Conclusions: Females were less likely to claim workers' compensation when compared to males even in occupational groups with a predominantly female workforce such as Hair and beauty. The gender discrepancy between the diagnosed disease dataset and the workers' compensation dataset requires further investigation as to why males were more likely to claim than females, particularly as the gender differences for diagnosed disease do not seem to follow the same pattern. A comprehensive surveillance system for OCD policy and practice intervention, should integrate diagnosed disease data and workers' compensation claims statistics.